The Library and Information Science educator: nurturing for strategic learning experiences - Osuchukwu, Ngozi; Wagwu, Victor (Folia Toruniensia, 2020)
Aim: The aim of this article was to highlight the experiences of Library and Information Science (LIS) educators in integrating strategies in library schools, examine the outcome of the experiences, identify the lessons learnt and ascertain the implications of the findings. Methods: This was a report of LIS Educators in Nigerian Library Schools. The activities were carried out in Madonna University, Nigeria and Ignatius Aguru University of Education, Rumuorlumeni, Port Harcourt, Rivers State, Nigeria. Fifteen LIS educators were involved in the activity. The method used were dialogues, focal group discussion, talk shows and presentation. The strategies were implemented from 2017 to 2019. Results: It was shown that LIS educators incorporated world book day, world literacy day, world language day, human rights anniversary, IFLA global vision, motivational and ICT trainings into the curriculum. The streaming and initiating of these activities stimulated interest in career charting of students as well as attracted more recognition and acknowledgement to LIS departments. The lessons learnt included craving from students and colleagues for more engaging programs, admiration from other departments and awareness creation for inclusive learning program. Conclusion: There is need to re-strategize the trainings and curriculum in library schools in order to remain relevant with global trends in information service. Therefore, updating the trainings and LIS education are very important in building vibrant career ready professionals. LIS is a serious business and the educators must keep the motor of change moving with stimulating dialogue and practices. This will help to produce professionals who will fit into the information society with career readiness.